Comparison of the Diagnostic Test of Leukocyte Count, Percentage of Neurtrophyl, and C-Reactive protein (CRP) in Adult Patients With Simple and Complicated Acute Appendicitis - Imam Sofii Agus Barmawi Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: acute appendicitis is one of the acute abdomen conditions that needs an emergency surgical procedure to prevent severe complication. If the perforation is present, the complications are general peritonitis, abscess and postoperative complication such as fistula and operative wound infection. Late diagnosis can increase the mortality and morbidity. There are about 11.2%-30% cases with intestinal perforation caused by late diagnosis. The leukocyte count, percentage of neutrophyl and C-reactive protein (CRP) are valuable informations to diagnose the perforation and nonperforation acute appendicitis in adult patients.Method: a prospective cross sectional study was held on diagnostic test from patient's database for acute appendicitis cases in Digestive Surgery Subdivision of Dr Sardjito Hospital from December 2005 until October 2006. The data was classified as simple and complicated acute appendicitis based on the histopathology result. Eighty two were found for both groups which fulfilled the inclusion and exclusion criteria. The diagnostic test Le. sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), Likelihood Ratio (LR +), Likelihood Ratio (LR-I, accuracy and receiver operating characteristics (ROC) with area under the curve (AUC) were analyzed for the leukocyte count, neutrophyl, and C-reactive protein (CRP) in each group with histopathology result as a gold standard.Result: the leukocyte count, neutrophyl and C-reactive protein (CRP) had respectively sensitivity of: 70,07%; 74,54%; 89,09%; specificity 70,37%; 70,37%; 81,48%; Positive Predictive Value (PPV): 82,97%; 83,67%; 90,74%; Negative Predictive Value (NPV) 54,28%; 57,57%; 78,57%; Likelihood Ratio (LR+) 2,36%; 2,51 %; 4,56%, Likelihood Ratio (LR-) 0,42%; 0,22%; 0,13%, area under the curve (AUC) 0,797; 0,744; 0,891, and accuracy 70,73%; 73,17%, 86,56%.Conclusion: C-reactive protein (CRP) was a better diagnostic test to differ simple from complicated acute appendicitis in adult patient compared to leukocyte count and neutrophy!.Key words: simple and complicated acute appendicitis, leukocyte cout, neutrophyl, C- reactive protein